Prenatal and postnatal lipid-based nutrient supplementation and cognitive, social-emotional, and motor function in preschool-aged children in Ghana: a follow-up of a randomized controlled trial - Ocansey, M.E.; Adu-Afarwuah, S.; Kumordzie, S.M.; Okronipa, H.; Young, R.R.; Tamakloe, S.M.; Oaks, B.M.; Dewey, K.G.; Prado, E.L. (American Journal of Clinical Nutrition, 2019)
Background Adequate nutrition is necessary for brain development during pregnancy and infancy. Few randomized controlled trials of supplementation during these periods have measured later developmental outcomes. Objective Our objective was to investigate the effects of provision of prenatal and postnatal lipid-based nutrient supplements (LNS) on child development at preschool age. Methods We conducted a follow-up study of 966 children aged 4–6 y in 2016, born to women who participated in the International Lipid-Based Nutrient Supplements-DYAD trial conducted in Ghana in 2009–2014, representing 79% of eligible children. Women ≤20 weeks of gestation were randomized to daily LNS or multiple micronutrient (MMN) capsules during pregnancy through 6 mo postpartum or iron and folic acid (IFA) capsules during pregnancy and calcium placebo capsules during 6 mo postpartum. Children in the LNS group received LNS from 6 to 18 mo. Primary outcomes of this follow-up study were (1) a cognitive factor score based on a test battery adapted from several standard tests, 2) fine motor score (9-hole pegboard test), and (3) social-emotional difficulties (Strengths and Difficulties Questionnaire; SDQ). Eight secondary outcomes were calculated in specific domains (e.g., language, SDQ prosocial). Analysis was by a complete case intention to treat in a 2-group comparison: LNS compared with non-LNS (MMN + IFA). Results Children in the LNS group had significantly lower social-emotional difficulties z-scores than children in the non-LNS group (adjusted for child age β = −0.12, 95% CI: −0.25, 0.02, P = 0.087; fully adjusted β = −0.16, 95% CI: −0.29, −0.03, P = 0.013). The effect of LNS on social-emotional difficulties score was larger among children living in households with lower home environment scores (P-interaction = 0.081). No other outcomes differed between the 2 intervention groups. Conclusions Provision of LNS during the first 1000 d of development improved behavioral function, particularly for children from low nurturing and stimulation households, but did not affect cognition at preschool age in this setting. Trial Registration: clinicaltrials.gov, Identifier NCT00970866.